Effect of Different Nutritional Materials on Laccase Activity and Biomass Accumulation of the Auricularia cornea var. Li Strain - Xue Xiong; Peng Li; Zhun Xiang; Yao-Wei He; Xuan Zheng; Zhong-Xuan Liu (BioResources)
The laccase activity changes of the Auricularia cornea var. Li strain were studied over a continuous 9-day period using different carbon sources, nitrogen sources, and lignocellulose as liquid fermentation inducers. The results showed that the addition of carbon sources, nitrogen sources, and alkaline lignin all stimulated Auricularia cornea var. Li to secrete laccase and promoted the accumulation of mycelial biomass. Both carbon and nitrogen deficiencies could stimulate Auricularia cornea var. Li to produce more laccase, but they were detrimental to the accumulation of mycelial biomass. Maltose and peptone should be prioritized as materials for cultivating high-laccase-producing Auricularia cornea var. Li strains through liquid fermentation. Lignocellulosic biomass could significantly enhance laccase activity in Auricularia cornea var. Li. During the cultivation of Auricularia cornea var. Li., wheat bran and cottonseed hulls that produced high levels of laccase should be recommended. This study partially revealed the laccase production characteristics of Auricularia cornea var. Li and identified culture substances that were beneficial for laccase secretion during different growth stages of the mushroom. The results provide a foundation for improving the yield and quality of Auricularia cornea var. Li.